2021
DOI: 10.1101/2021.01.07.21249396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutations that confer resistance to broadly-neutralizing antibodies define HIV-1 variants of transmitting mothers from that of non-transmitting mothers

Abstract: Despite considerable reduction of mother-to-child transmission (MTCT) of HIV through use of maternal and infant antiretroviral therapy (ART), over 150,000 infants continue to become infected with HIV annually, falling far short of the World Health Organization goal of reaching <20,000 annual pediatric HIV cases worldwide by 2020. Prior to the widespread use of ART in the setting of pregnancy, over half of infants born to HIV-infected mothers were protected against HIV acquisition. Yet, the role of maternal … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 84 publications
0
3
0
Order By: Relevance
“…We previously demonstrated that autologous HIV viruses isolated from transmitting mothers and their infected infants were enriched with genetic motifs that were associated with resistance to bnAbs (59), suggesting that acquired plasma neutralization-resistance is a common feature of vertically transmitted variants. We also demonstrated that an in uterotransmitted virus from a mother with plasma V3 glycan-specific bnAb activity was selected for its ability to escape the mother's dominant bnAb specificity (41).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that autologous HIV viruses isolated from transmitting mothers and their infected infants were enriched with genetic motifs that were associated with resistance to bnAbs (59), suggesting that acquired plasma neutralization-resistance is a common feature of vertically transmitted variants. We also demonstrated that an in uterotransmitted virus from a mother with plasma V3 glycan-specific bnAb activity was selected for its ability to escape the mother's dominant bnAb specificity (41).…”
Section: Discussionmentioning
confidence: 99%
“…We previously demonstrated that autologous HIV viruses isolated from transmitting mothers and their infected infants were enriched with genetic motifs that were associated with resistance to bnAbs (59), suggesting that acquired plasma neutralization-resistance is a common feature of vertically transmitted variants. We also demonstrated that an in utero-transmitted virus from a mother with plasma V3 glycan-specific bnAb activity was selected for its ability to escape the mother’s dominant bnAb specificity (41).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon could be explained by the observation that among HIV-infected women who have plasma bnAb activity, bnAb-resistant variants circulating in their blood may be selected as infant transmitted/founder variants (Martinez et al, 2020;Tu et al, 2022). Indeed, transmitting mothers carry mutations in their circulating viral population that are associated with bnAb escape (Kumar et al, 2021), indicating that bnAb escape variants have a propensity for vertical transmission. An association of pre-existing infant ADCC with reduced HIV-1 acquisition and lower morbidity has also been reported (Thomas et al, 2021), supporting the role of Fc-mediated effector antibodies in modifying infant HIV acquisition risk and outcome.…”
Section: Impact Of Placentally-transferred Antibodies Against Neonata...mentioning
confidence: 99%